Standing wave impacts on vertical hydraulic structures with overhangs for varying wave fields and configurations - De Almeida, Ermano; Hofland, Bas (Journal of Coastal and Hydraulic Structures, 2021)
This study focuses on standing wave impacts on vertical hydraulic structures with relatively short overhangs. It addresses the demand for extended knowledge and loading prediction expressions for these structures. Based on laboratory experimental data from 146 tests, this paper works on two complementary objectives. Firstly, this study extends the knowledge on this type of wave impacts addressing the following aspects: changes in hydraulic loading conditions (regular/irregular waves and varying freeboards) and changes in the structure geometry (lateral constriction and loading reducing ventilation gaps). All laboratory tests consider relatively short overhangs, with ratios of wave length to overhang length between 10 and 40, and ratios of overhang height to overhang length of 3 and 6. The regular wave tests showed that the tests with the longer overhang were related to longer impact durations and larger loading variability compared to the tests with the shorter overhang. Also, tests with reduced freeboards produced larger impact loads. In addition, repeated tests presented equal impulse values (I, Beta, td, Lambda). Furthermore, the pressure peaks measured at one location were found to not represent the pressure peaks averaged over the structure width, while the pressure-impulses measured at one location were found to properly represent the pressure-impulses averaged over the width. The constriction tests showed that a lateral constriction amplifies pressure peaks and pressure-impulses at the constriction edge. The ventilation gap tests showed that ventilation gaps are effective in reducing force peaks and force-impulses. The irregular wave tests highlighted that the dynamic interactions of the incident waves with the structural configurations are even more dynamic and variable in tests with irregular wave conditions. Secondly, this study presents loading prediction expressions for preliminary loading estimations built up by the previously developed pressure-impulse theory that is empirically calibrated using the presently acquired experimental data. To that end, the relation between the effective bounce-back factor (1<Beta<2) with the Gamma Parameter is described. These loading prediction expressions may be used for preliminary load estimations and in combination with structural response models.